The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.7759/cureus.7308
|View full text |Cite
|
Sign up to set email alerts
|

Pseudobulbar Affect Presenting as Hypomania

Abstract: Pseudobulbar affect (PBA) is a behavioral syndrome associated with various neurological conditions that typically manifests as uncontrollable laughing or crying. PBA can significantly impact the quality of life of patients affected as these spells can be inappropriate to the social setting or incompatible with the patient's emotional state. The underlying mechanism of PBA appears to be associated with disinhibition in neuronal pathways involving dopamine, serotonin, and glutamate, but the exact mechanism remai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Furthermore, evidence suggests that abnormal dopaminergic, glutamatergic, and serotonergic neurotransmission may also play a role in the development of PBA [1]. Recent neuroimaging studies have demonstrated a reduction in dopamine and serotonin expression, along with increased glutamate neurotransmission within the corticopontine-cerebellar pathways [9]. It is suggested that treatment approaches may involve increasing dopamine and serotonin levels while reducing glutamate neurotransmission [9].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, evidence suggests that abnormal dopaminergic, glutamatergic, and serotonergic neurotransmission may also play a role in the development of PBA [1]. Recent neuroimaging studies have demonstrated a reduction in dopamine and serotonin expression, along with increased glutamate neurotransmission within the corticopontine-cerebellar pathways [9]. It is suggested that treatment approaches may involve increasing dopamine and serotonin levels while reducing glutamate neurotransmission [9].…”
Section: Discussionmentioning
confidence: 99%
“…Imaging studies have shown a reduction in dopamine and serotonin neurotransmission and an increase in glutamate neurotransmission. Therefore, treatment entails increasing dopamine and serotonin neurotransmission and reducing glutamate neurotransmission [7].…”
Section: Discussionmentioning
confidence: 99%
“…Delirium is a disturbance of consciousness, and this patient does not fall into this category because he had not demonstrated a decreased level of consciousness. PBA is a behavioral syndrome associated with various neurological conditions that typically manifests as uncontrollable laughing or crying (Espiridion et al, 2020). This patient is not considered to have PBA because, although he had emotional upsets, he did not laugh or cry nonstop.…”
Section: Differential Diagnosismentioning
confidence: 99%